PENGETAHUAN DAN SIKAP BIDAN MENGENAI PENGGUNAAN PARTOGRAF DALAM PERSALINAN DI PUSKESMAS PONED KOTA MANADO - Toemandoek, Jacqueline P.; Wagey, Freddy; Loho, Maria (Universitas Sam Ratulangi, 2015)
Abstract: The high maternal mortality rate is mostly due to pregnancies and labours. Health workers who can help labour are inter alia midwives. A health center that has the facilities and the ability to provide 24-hours services to cope emergency cases of obstetric and neonatal care is called PONED Public Health Center (PHC). This study aimed to obtain the knowledge and attitude of midwives about partograph in PONED PHCs in Manado. There were 33 respondents of 6 PONED PHCs in Manado. The results showed that most of the midmives (90.9%) in PONED PHCs had good knowledge about the usage of pantograph in labour; 2 respondents (6.1%) had fair knowledge, and 1 respondent (3.0%) had poor knowledge. All midwives (100%) had positive attitude about the usage of partograph. Conclusion: Most midwives in PONED PHC in Manado had good knowledge and positive attitude about the usage of partograph in labour.Keywords: midwives, PONED Public Health Center, partographAbstrak: Tingginya angka kematian ibu terutama pada saat kehamilan dan persalinan. Tenaga kesehatan yang dapat menolong persalinan yaitu salah satunya bidan. Puskesmas yang memiliki fasilitas dan kemampuan memberikan pelayanan untuk menanggulangi kasus kegawatdaruratan obstetrik dan neonatal selama 24 jam yaitu puskesmas PONED. Pada penelitian ini terdapat 33 responden dari 6 puskesmas PONED di Kota Manado. Hasil penelitian memperlihatkan bahwa tingkat pengetahuan bidan tentang penggunaan partograf dalam persalinan di Puskesmas PONED Kota Manado umumnya (90,9%) baik, 2 responden (6,1%) cukup, dan 1 responden (3,0%) kurang. Mengenai distribusi sikap, semua bidan (100%) mempunyai sikap positif. Simpulan: Umumnya bidan di puskesmas PONED Kota Manado mempunyai pengetahuan yang baik dan sikap yang positif mengenai penggunaan partograf dalam persalinan.Kata kunci: bidan, puskesmas PONED, partograf